2021
DOI: 10.3389/fpsyt.2021.789982
|View full text |Cite
|
Sign up to set email alerts
|

Viloxazine in the Treatment of Attention Deficit Hyperactivity Disorder

Abstract: Attention deficit hyperactivity disorder (ADHD) is the most common neurodevelopmental disorder in children. Over the past twenty years, research on the disease and its characteristics and treatment options has grown exponentially. The first-line pharmacologic treatment of ADHD is stimulants, which have a response rate of ~70%. With the support of four phase 3 studies involving more than 1,000 pediatric patients 6–17 years old, the FDA has approved the non-stimulant, serotonin-norepinephrine modulating agent (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In one of the phase III studies (NCT03247543), 4 patients reported suicidal ideation as per C-SSRS (n = 3 [2.8%], 200 mg/d; n = 1 [1%], 400 mg/d). In contrast, no suicidal ideation as per C-SSRS was reported in the 2 viloxazine ER Studies in Adolescents (12)(13)(14)(15)(16)(17) Efficacy assessment. Two phase III studies (NCT03247517 and NCT03247556) evaluated the efficacy of viloxazine ER in adolescents diagnosed with ADHD.…”
Section: Studies In School-age Children (6-12 Years)mentioning
confidence: 85%
See 2 more Smart Citations
“…In one of the phase III studies (NCT03247543), 4 patients reported suicidal ideation as per C-SSRS (n = 3 [2.8%], 200 mg/d; n = 1 [1%], 400 mg/d). In contrast, no suicidal ideation as per C-SSRS was reported in the 2 viloxazine ER Studies in Adolescents (12)(13)(14)(15)(16)(17) Efficacy assessment. Two phase III studies (NCT03247517 and NCT03247556) evaluated the efficacy of viloxazine ER in adolescents diagnosed with ADHD.…”
Section: Studies In School-age Children (6-12 Years)mentioning
confidence: 85%
“…Also, viloxazine has been used as an antidepressant and anxiolytic medication in adults in Europe for at least 2 decades. 12 It is thus hypothesized that viloxazine ER may be beneficial in patients with ADHD with comorbid conditions such as anxiety disorders and/or depression. Studies directly assessing the efficacy and safety of viloxazine ER in patients with ADHD with specific comorbid conditions (eg, substance abuse disorder, mood disorder, anxiety) are required to make firm recommendations.…”
Section: Relevance To Patient Care and Clinical Practice In Compariso...mentioning
confidence: 99%
See 1 more Smart Citation
“…Viloxazine is a selective norepinephrine reuptake inhibitor with activity in the noradrenergic and serotonergic pathways [ 233 ], is approved to be used in the treatment of ADHD children and adolescents and is administered orally in once-daily oral doses [ 234 ]. One possible action mechanism for viloxazine against ADHD is through increased efflux of norepinephrine and dopamine in the prefrontal cortex [ 235 ].…”
Section: Adhd and Epilepsy: Challenges And Opportunitiesmentioning
confidence: 99%
“…One possible action mechanism for viloxazine against ADHD is through increased efflux of norepinephrine and dopamine in the prefrontal cortex [ 235 ]. Viloxazine has no drug interactions with LDX or MPH [ 233 , 236 ]. Adverse effects include somnolence, sedation, headache, fatigue, decreased appetite, abdominal pain, upper respiratory infection, nausea and vomiting, cardiovascular effects and suicidal ideation.…”
Section: Adhd and Epilepsy: Challenges And Opportunitiesmentioning
confidence: 99%